Genetics of earliness in fenugreek under powdery mildew inoculated and natural environments - Jatasra, R Avtar, A S Rathi, D S (Journal of Spices and Aromatic Crops, 2003)
Inheritance of days to flower and maturity in fenugreek (Trigonella foenum-graecum L.) was studied using six generations (P1, P2, FI, F2, B1 and B2) of a cross between HM 350 (early) and HM65 (late) in two different environments ie. inoculated with conidia of powdery mildew disease (E1) and normal (E2). Partial dominance was observed for both the traits under both the environments. The variances of F2 and backcross generations revealed the predominance of non-additive gene action. Genetic analysis suggested that generally all types of epistatic effects were significant for both the traits studied in one environment or another. Intermating of selects in early generations has been suggested for further improvement in these traits.